2004
DOI: 10.1523/jneurosci.2833-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Posterior Parietal Cortex Interferes with Arm Trajectory Adjustments during the Learning of New Dynamics

Abstract: Substantial neurophysiological evidence points to the posterior parietal cortex (PPC) as playing a key role in the coordinate transformation necessary for visually guided reaching. Our goal was to examine the role of PPC in the context of learning new dynamics of arm movements. We assessed this possibility by stimulating PPC with transcranial magnetic stimulation (TMS) while subjects learned to make reaching movements with their right hand in a velocity-dependent force field. We reasoned that, if PPC is necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
103
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 44 publications
(43 reference statements)
15
103
1
Order By: Relevance
“…The combined results of this and other studies (Chib et al, 2009;Della-Maggiore et al, 2004;Vesia et al, 2010) identify this region as a key area for processing proprioceptive information for motor control. Furthermore, this region can be clearly distinguished from an area around the anterior IPS, which is crucial for online sensorimotor processing in the presence of visual feedback about the hand position.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…The combined results of this and other studies (Chib et al, 2009;Della-Maggiore et al, 2004;Vesia et al, 2010) identify this region as a key area for processing proprioceptive information for motor control. Furthermore, this region can be clearly distinguished from an area around the anterior IPS, which is crucial for online sensorimotor processing in the presence of visual feedback about the hand position.…”
Section: Introductionsupporting
confidence: 64%
“…This finding complements the studies based on which we included mIPS posterior into the current study. Della-Maggiore et al (2004) have shown that TMS applied over this area also interferes with the learning of novel dynamics induced by a force field, and Chib et al (2009) have demonstrated that this area is important for tracking the movement of a manipulandum in the absence of visual feedback. In both studies, processing of proprioceptive information was the key for successful task execution as in our proprioception-only condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This imaging study also found that adaptation involved cerebral cortical structures, including primary motor and somatosensory cortices and posterior parietal cortex (PPC). The latter cortical area has also been investigated by Della-Maggiore et al (2004), who found that single-pulse TMS applied over the PPC after movement onset impaired adaptation to a curl field relative to controls. Therefore, the evidence from the human literature suggests that dynamic motor adaptation involves a cerebello-thalamocortical circuit.…”
Section: Introductionmentioning
confidence: 99%